Omalizumab in children with severe allergic disease: a case series - Giuseppe Crisafulli; Lucia Caminiti; Fernanda Chiera; Stefania Arasi; Giuseppina Salzano; Ilenia Panasiti; Andrea Barbalace; Giovanni Battista Pajno (BMC, 2019)
Abstract Background Currently, severe allergic asthma and food allergy in children represent an important public health problem with medical, psychosocial and economic impacts. Omalizumab is a humanized monoclonal anti-IgE antibody, approved for refractory allergic asthma and chronic urticaria. It has been widely used in clinical practice as add-on therapy in patients with severe uncontrolled allergic asthma. In recent years there has seen the emergence of an allergic epidemic with increasing food allergy, which represents the main cause of anaphylaxis in children. The standard of care for food allergy is strictly dietary allergen avoidance and emergency treatment, but recent clinical trials have suggested that omalizumab may have a role to play as an adjuvant to oral immunotherapy (OIT). We present a case series of patients treated at our institution with omalizumab for severe allergic asthma and food allergy. Methods Patients received omalizumab according to a standard reference nomogram after failing standard therapies. In children with comorbid severe food allergy, omalizumab was administered in conjunction with an oral immunotherapy protocol. Results Omalizumab was effective in controlling symptoms of allergic asthma, allergic rhinitis and rhinosinusitis, but not eosinophilic esophagitis, while aiding successful oral desensitization of comorbid severe food allergies. Conclusions Omalizumab appears to be an excellent therapeutic option in children with inadequately controlled severe allergic asthma, allergic rhinitis and rhinosinusitis, with or without food allergy.